EFEKTIVITAS PENGGUNAAN PUPUK BOKASHI JERAMI DAN PUPUK ANORGANIK DALAM MENINGKATKAN PERTUMBUHAN DAN HASIL TANAMAN PADI (Oryza sativa L.) VARIETAS CIHERANGâ€ - Muharam, Muharam; Purnomo, Sulistyo Sidik (Majalah Ilmiah SOLUSI, 2013)
The objective of the experiment was find out the influence of different dozen of bokashi organic fertilizer and anorganic fertilizer to growth and yield of Ciherang variety. The experiment was conducted at field experiment of Ciwaringin Village â€“ karawang district, West Java in dry seasons 2011 The experiment was arranged in the factorial methode of Randomized Block Design with three replication and twenty six of different dozen bokashi organic fertilizer and anorganic fertilizer combination. The first factor is bokashi application with four degree of application : j0=0 ton/ha bokashi, j1=3 ton/ha bokashi, j2=5 ton/ha bokashi and j3= 7 ton/ha bokashi. The second factor is anorganic fertilizer application with tree of degree n1 = 67,5 kg/ha N + 22,5 kg/ha P2O5 + 22,5 kg/ha K2O , n2 = . 135 kg/ha N + 45 kg/ha P2O5 + 45 kg/ha K2O dan n3 = 202,5 kg/ha N + 67,5 kg/ha P2O5 + 67,5 kg/ha K2O The experiment result showed that no have of interaction between different dozen bokashi organic fertilizer and anorganic fertilizer to all of variable. The single effect of bokashi fertilizer was influence of tiller number at 70 HST, number and yield. The single effect of anorganic fertilizer was increased of tiller number, panicle number, grain number per panicle, percentase of grain and yield The bokashi application with 7 ton/ha showed highest yield (9,8 t/ha) at the anorganic application with 202,5 kg/ha n + 67,5 kg/ha p2o5 + 67,5 kg/ha K2O but not significance at the anorganic application 135 kg/ha N + 45 kg/ha P2O5 + 45 kg/ha K2O with 9.7 ton/ha yield.